Swiss foreign policy : foundations and possibilities - Goetschel, Laurent (Routledge, 2005)
The book is essential reading to all those interested in foreign policy analysis, the relationship between democracy and international relations, the significance of being a small state in contemporary Europe and the specificities of the Swiss.